2013
DOI: 10.1007/s00707-013-0936-9
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of microstructured continua from lattice systems via principle of virtual works: the case of masonry-like materials as micropolar, second gradient and classical continua

Abstract: The description of the mechanical behaviour of brick/block masonry through equivalent continua is presented here as a paradigmatic example of the problem of gross modelling of discontinuous and heterogeneous materials as continua with microstructure. The approaches reported in the literature differ for the way identification of the continuum is carried out or the nature of the continuum itself. In this paper, continuous models equivalent to rigid particle systems with free or constrained rotations are derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
89
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 52 publications
1
89
0
Order By: Relevance
“…This implies that the micropolar effects cannot be neglected in the presence of non-symmetric strain and shear effects. Like in the extensively investigated case of anisotropic periodic materials [18,24], further confirmations of the suitability of micropolar model are expected with the investigation of media with particles of different shapes and also with the investigation of non-linear constitutive behaviors.…”
Section: Final Remarksmentioning
confidence: 86%
“…This implies that the micropolar effects cannot be neglected in the presence of non-symmetric strain and shear effects. Like in the extensively investigated case of anisotropic periodic materials [18,24], further confirmations of the suitability of micropolar model are expected with the investigation of media with particles of different shapes and also with the investigation of non-linear constitutive behaviors.…”
Section: Final Remarksmentioning
confidence: 86%
“…For micropolar continuum see for example Masiani et al (1995), Masiani and Trovalusci (1996), Boutin (1996), Sulem and Mühlhaus (1997), Smyshlyaev and Cherednichenko (2000), Forest et al (2001), Casolo (2009), Salerno and De Felice (2009), Addessi et al (2010), De Bellis and Addessi (2011) and Pau and Trovalusci (2012). For higher order continuum see for example Stefanou et al (2010), Bacigalupo and Gambarotta (2012) and Trovalusci and Pau (2014).…”
Section: Introductionmentioning
confidence: 97%
“…In this section the works of Salerno and De Felice (2009), Pau and Trovalusci (2012) and Trovalusci and Pau (2014) are chosen as benchmark. In these papers the problem of Cauchy and micropolar equivalent continua is dealt with.…”
Section: Introductionmentioning
confidence: 99%
“…In [54], it is shown that the virtual power format can be so generalized as to deduce the balance laws of three-dimensional thermomechanics. On the other side, in [70,77] it has been shown that the Principle of Virtual Powers (PVP) can be expedient to perform coarse-graining procedures in the framework of the homogenization techniques. These corpuscular-continuous approaches are based on the assumption that a selected microscopic level structure of matter can be described as discontinuous, and that the transition from the coarse scale is governed by an a priori map between the large set of degrees of freedom od discrete systems and the deformation fields of the continuum.…”
Section: Introductionmentioning
confidence: 99%
“…A model within the framework of generalized continuum mechanics, as the one we propose, may be computationally efficient, provided that a proper physical meaning of the additional fields is proposed and a constitutive identification for the internal and the external actions is performed [74,64,69,4,27,51,5,2,77]. In the present model, on the purely mechanical side, in addition to the standard displacement field, we consider a kinematical microstructural field, representing the mean jump of the displacement field due to the presence of microcracks; on the thermal side, we not only consider the thermal displacement, a nonstandard thermal state variable firstly considered by Helmholtz, but we also introduce an additional microstructural kinetic variable, whose time derivative represents the mean jump of the temperature field due to the presence of microcracks, and that we can call microtemperature.…”
Section: Introductionmentioning
confidence: 99%